Oxford handbook of oral and maxillofacial surgery - Cascarini, Luke; Schilling, Clare; Gurney, Ben; Brennan, Peter ([Oxford] : Oxford University Press, 2018)
This second edition of the'Oxford Handbook of Oral and Maxillofacial Surgery' has been fully updated to cover the current guidelines and research in the field of oral and maxillofacial surgery (OMFS). Splitting vital knowledge into chapters based on clinical areas, this handbook uses bulleted lists and summary boxes to make the information easily searchable.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on CIP data; resource not viewed.
Keywords: Face -- Surgery; Mouth -- Surgery